2018
DOI: 10.1098/rspb.2018.1702
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of sex change for effective population size

Abstract: Sequential hermaphroditism, where males change to females (protandry) or the reverse (protogyny), is widespread in animals and plants, and can be an evolutionarily stable strategy (ESS) if fecundity rises faster with age in the second sex. Sequential hermaphrodites also generally have sex ratios skewed towards the initial sex, and standard theory based on fixed sexes indicates that this should reduce effective population size (N e ) and increase the deleterious effects of genetic drift. We show that despite ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Indeed, we often tend to oversimplify the complexity of sequential hermaphroditism: not all protogynous species are haremic, as not all protandrous species mate in pairs. A recent study 28,85 has revealed a broader variation in effective population size in protogynous species that differs from the more limited expectations obtained when all protogynous species were considered haremic by default. Instead, some protogynous species were found to be group spawners, altering the expectations that all protogynous species should have low effective population size due to their supposed haremic system.…”
Section: Discussionmentioning
confidence: 81%
“…Indeed, we often tend to oversimplify the complexity of sequential hermaphroditism: not all protogynous species are haremic, as not all protandrous species mate in pairs. A recent study 28,85 has revealed a broader variation in effective population size in protogynous species that differs from the more limited expectations obtained when all protogynous species were considered haremic by default. Instead, some protogynous species were found to be group spawners, altering the expectations that all protogynous species should have low effective population size due to their supposed haremic system.…”
Section: Discussionmentioning
confidence: 81%
“…The very high N e /generation values obtained for the white seabream seemingly contradict this prediction (Table 2). This expected lower N e was also challenged in recent studies with protogynous species over historical timescales (Coscia et al, 2016), and in analysis of an eco-evolutionary model with ten hypothetical species (Waples, Mariani & Benvenuto, 2018).…”
Section: Estimates Of Contemporary Effective Population Sizementioning
confidence: 97%
“…[ 59 ] A recent study shows that biased sex ratios in sequential hermaphrodites have surprisingly little effect on their population effective size and thus evolvability. [ 60 ] We can speculate that similar processes concern ESD species as well. Their biased sex ratios might not be optimal for the individual fitness but advantageous for long‐term survival of the lineage, a situation that creates an interesting case of conflict between individual selection and selection at higher levels.…”
Section: Adaptive Values Of Gsd and Esd: Is Esd A Short‐lived Strategy?mentioning
confidence: 98%